The Effect Of Work Discipline and Organizational Culture on Employee Performance In The Youth and Sports Tourism Service in Seluma Regency - Irana Dewi; Ida Ayu Made Er meytha Gayatri; Sri Handayani (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
This study aims to determine the effect of work discipline and organizational culture on employee performance at in the Youth and Sports Tourism Service in Seluma Regency. Samples were 35 Civil Servants and honorary employees, data was collected using a questionnaire and the analytical method used was multiple linear regression, hypothesis testing and coefficient of determination test. From the research results obtained multiple linear regression equation Y = 8.306 + 0.464X1 + 0.372 X2 + 4.788, Work discipline has a significant effect on employee performance, this is evidenced by the results of partial hypothesis testing (t test) that the calculated t value (3.169) is greater than t table (1.692) and a significance value of 0.003 is less than 0.05, Organizational culture has a significant effect on employee performance, this is evidenced by the results of partial hypothesis testing (t test) that the t count (2.801) is greater than t table (1.692) and a significance value of 0.009 is less than 0.05, Work Discipline and Organizational Culture have a jointly significant influence on Employee Performance this is evidenced by the results of simultaneous hypothesis testing (test F) that the calculated F value (29.121) is greater than F table (3.29) and a significant value of 0.000 is less than 0.05. The coefficient of determination is 0.645, meaning that work discipline (X1) and organizational culture (X2) contribute 64.5% to performance (Y), while the remaining 35.5% is influenced by other variables not examined.